Experimental Investigation on Bituminous Mixes with MoRTH Gradation and Superpave Gradation - Simron Rajkumar.J, Samuel; M.M, Vijayalakshmi.; S, Lakshmi (International Journal of Engineering and Technology, 2018)
The shape of aggregates particle has a significant influence on the performance of an asphalt pavement (Patrick, 2003).Â More percentage of flaky and elongated aggregates makes the mix to be harsh and leads in delay during the construction process. (Mathew, 2006). Hence it is felt that the study on the effect of the shape of aggregates on bituminous mixtures is relevant and essential. In bituminous mixtures, it is mandatory to maintain certain level of air voids to avoid the failure due to binder expansion during hot periods. The voids present in a compacted mix depend on the shape of the aggregates (Sridhar. et al), highly angular, flaky and elongated aggregates have more voids in comparison with rounded aggregates. In order to overcome the effect of shape of an aggregate,Â an investigation has been carried out to assess the performance of the bituminous mix under various properties. For finding the exact variation among the mixes, the volumetric analysis have been carried with fatigue and moisture sensitivity test. The result shows the superior performance in Superpave gradation when compared with MoRTH gradation. The optimum percentage of bitumen is 0.2% decrement corresponding to 4% of air-voids in Superpave graded mix.Â Â